146k views
4 votes
2x² - 7x + 3 = 0 solve the quadratic equations by using the quadratic formula​

User Menkot
by
5.4k points

2 Answers

5 votes

Answer:

x = 3

x =1/2

Explanation:


2x^2-7x+3=0\\\\x_1 ,2 =(-b\pm √(b^2-4ac))/(2a)\\\\\mathrm{For\:}\quad a=2\\\:b=-7\\,\:c=3\\:\quad x_(1,\:2)=(-\left(-7\right)\pm √(\left(-7\right)^2-4*\:2*\:3))/(2*\:2)\\\\=(7+√(\left(-7\right)^2-4*\:2*\:3))/(2*\:2)\\\\7+√(\left(-7\right)^2-4*\:2*\:3)=7+√(25)\\\\=(7+√(25))/(2*\:2)\\\\=(7+√(25))/(4)\\\\√(25)=5\\\\=(7+5)/(4)\\\\=(12)/(4)\\\\=3 \\


x=(-\left(-7\right)-√(\left(-7\right)^2-4*\:2*\:3))/(2*\:2)\\\\=(7-√(\left(-7\right)^2-4*\:2\cdot \:3))/(2*\:2)\\\\7-√(\left(-7\right)^2-4* \:2*\:3)=7-√(25)\\\\=(7-√(25))/(2* \:2)\\\\=(7-√(25))/(4)\\√(25)=5\\\\=(7-5)/(4)\\=(2)/(4)\\\\=(1)/(2)

User Oliver Jones
by
5.6k points
2 votes

Answer:

x = 1/2 or 3

Explanation:

Compare the given equation to the standard form equation to identify the values of the variables in the formula. Then put those values in the formula and do the arithmetic.


ax^2+bx+c=0\\\\2x^2-7x+3=0\\\\a=2;\ b=-7;\ c=3\\\\x=(-b\pm√(b^2-4ac))/(2a)\\\\x=(-(-7)\pm√((-7)^2-4(2)(3)))/(2(2))=(7\pm√(25))/(4)=(7\pm 5)/(4)\\\\x=\left\{(1)/(2),3\right\}

User Ashokds
by
5.4k points